Analysis of the effect of human capital investment on company performance - Masuluke, Matimba Faith (My University, 2019)
This research examines the effect of human capital investment on the firm’s performance in South African companies. This research is important given that the human asset has been proven to be one of the most important assets in the organisation and therefore this research set out to examine whether human assets actually contribute to the performance of the firm in the Johannesburg Stock Exchange Social Responsible index (SRI). Therefore the objective of this research was to examine the relationship between human capital investment and firm performance in terms of sales turnover, share price and net profit. Secondary data on human capital investment and companies’ performance (sales turnover, net profit and share price) were collected from integrated report archives of the 28 best performing companies in the JSE SRI Index for the six years from 2010 to 2015. The theoretical foundation was on the human capital theory and related previous literature. The research adopted a quantitative paradigm and applied the regression statistics, which were analysed with the aid of the excel software. Findings from the regression analysis indicate p value of 0.04 for HCI and sales turnover, p value of 0.69 for HCI and the share price and p value of 0.16 for HCI and net profit. This therefore, means that, within the sample of companies, there is a significant relationship between human capital investment and sales turnover of firms and no significant relationship between human capital investment and share price, and net profit of companies. This finding indicates that the result may change from negative to positive with a longer period of data. Over the long term companies that invest in HC would experience profitability (within a range of 10 to 13 years) (Blundell et al, 1999).This means that future research should use a longer period of data and include more companies outside of the JSE SRI Index companies. The research recommends that there is a need for companies to invest in human capital to improve companies’ performance and to win customers’ confidence.
Thesis (MBA.) -- University of Limpopo, 2019
Keywords: Human Capital Investment; Net profit; Financial performance; Sales turnover; Share price; Profit; Human capital -- South Africa; Investments; Corporate profits